Notes on biology of Brazilian populations of ants of the Pachycondyla foetida species complex (Formicidae: Ponerinae) - Itanna Oliveira Fernandes (Universidade Estadual de Feira de Santana, 2014)
In ants, biology studies are especially important to complete the information aiming to identify species belonging to unresolved or confused taxa in taxonomy. Such observations allow the inclusion of biological data with other characteristics of determined group, something that preserved specimens in collections do not reveal, such as nesting site, foraging time, nuptial flight and especially the relationship between castes, supporting taxonomic analysis and descriptions. Here, nests of three species of the complex foetida of the genus Pachycondyla were observed and collected in three Brazilian localities. Pleometrosis, secondary monogyny and cannibalism were observed for the ant P. inversa. In many ant species, queens newly mated are associated with other queens to establish new colonies, independent of parenthood. In the ant genus Pachycondyla, the reproductive structure varies broadly and aggressiveness seems to be an important factor in structuring the organization and reproductive division in the colony. The occurrence of males in nests of P. inversa and P. curvinodis allowed the description of males. The nuptial flight period was estimated to of P. inversa (August), P. villosa (October) and P. curvinodis (November).